POTENSI DAN STRATEGI PENGEMBANGAN PARIWISATA SAAT PANDEMI COVID-19 DI INDONESIA - Syahrudin, Dede; Rahmawati, Rita; Luthfie, Muhammad (Administratie: Jurnal Administrasi Publik, 2022)
This study aims to depict the potential and analyze tourism development strategies in Sukabumi Regency within the context of the Covid-19 pandemic. The research method employed is descriptive and a qualitative case study approach. The findings of the study indicate that tourism potential in Sukabumi Regency is highly diverse and innovative, bolstered by favorable geographical conditions such as abundant natural resources and a variety of tourism attractions known as GURILAPS, which stands for Mountains, Jungles, Seas, Beaches, and Rivers. The presence of the Ciletuh Palabuhanratu UNESCO Global Geopark (CPUGG) since 2019 has further enhanced Sukabumi Regency's recognition. However, in terms of tourism development both prior to and during the pandemic, the Tourism Office has yet to optimize the formulation of policies, programs, or development strategies, despite them being outlined in the Sukabumi Regency Tourism Office's 2016-2021 strategic plan. This shortcoming arises from the lack of effectiveness in the planning, implementation, and program execution processes, leading to insufficient enhancement of tourist attractions, branding, and visitor numbers. Consequently, the local community has not experienced notable progress in tourism management, development, and advancement that could bring about well-being and increased income, although they still feel secure and comfortable while engaging in tourism activities amid the Covid-19 pandemic.